Accessibility Challenges in Islamic Education in Indonesia: The Relevance of the Interpretation of al-Mujadilah Verse 11 in the Digital Era - Ahmad Najibul Firdaus (AL-Qiyadah, 2025)
This research presents a study that focuses on the challenges faced by the development of Islamic Education especially in Indonesia, viewing them as obstacles to be overcome for improvement. Specifically, it addresses the lack of equitable distribution of facilities and infrastructure within Islamic Education institutions in utilizing digital media during the digital era. This inequity impacts both the institutions themselves and their students. The method used in this research is library research, which is then analyzed through the interpretive lens of Islamic scholars' perspectives on Chapter al-Mujadilah verse 11. This verse offers solutions from the Quran, the primary source of Islamic law. Several scholars interpreting this verse argue that, while it was originally addressed to gatherings of knowledge, specifically during the time of the Prophet Muhammad, it can be interpreted with meanings more relevant to contemporary societal life. The research findings indicate that good Muslims possess tafassuh, a characteristic of being open-minded and generous towards others. This entails being willing to provide assistance to the less fortunate, offering benefits to the surrounding community, and making positive contributions.